2020
DOI: 10.1177/2374373520924190
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Patient Experience and Quality and Utilization of Primary Care Services

Abstract: We lack knowledge on how patient-reported experience relates to both quality of care services and visit attendance in the primary care setting. Therefore, in a cross-sectional analysis of 8355 primary care patients from 22 primary care practices, we examined the associations between visit-triggered patient-reported experience measures and both (1) quality of care measures and (2) number of missed primary care appointment (no shows). Our independent variables included both overall patient experience and its sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Little attention is given to social factors, parental well-being, anxiety or other non-physiologic aspects of disease. Careful consideration and study could determine if including these factors in discharge instructions could be one component of a multifactorial effort to improve family-centered emergency care to improve patient and family experience, revisits and outcomes (25, 26).…”
Section: Discussionmentioning
confidence: 99%
“…Little attention is given to social factors, parental well-being, anxiety or other non-physiologic aspects of disease. Careful consideration and study could determine if including these factors in discharge instructions could be one component of a multifactorial effort to improve family-centered emergency care to improve patient and family experience, revisits and outcomes (25, 26).…”
Section: Discussionmentioning
confidence: 99%
“…7 It has been suggested that patient experiences and patient outcomes are linked, with better patient experience increasing the likelihood of good clinical outcomes. 8 Furthermore, Aysola et al 9 suggested that in a primary care setting, better patient experience decreases the likelihood of a patient not attending future appointments. This is supported by Goldman et al 10 who demonstrated that a negative patient experience correlates strongly with future non-attendance.…”
Section: Development and Pilot Of A Community Low-vision Service-spec...mentioning
confidence: 99%
“…2 As positive patient experience and perceived level of care is a considerable predictor of recurrent utilization of health care services, it is important to analyze experiences of telehealth as a modality shift for diabetes management, particularly the probable impact either in disadvantages or benefits, as perceived by PWD. 10 A preliminary review of the literature has revealed a varied focus and methodological approach to the impact of telehealth care delivery for PWD during COVID-19. The vast majority of literature focused on quantitative data on biometric changes as proposed consequences of limited face-to-face consultations.…”
Section: Introductionmentioning
confidence: 99%